Herpes Zoster Masquerading as Acute Coronary Syndrome - Ishrat Hussain Dar (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2015)
A 65 year old male presented to the causality department of our hospital with one day history of burning chest pain in the right upper half of the chest radiating to the right axilla & the left precordial region associated with diaphoresis. No history of fever, cough or rash was evident. Vitals were normal. An X ray chest done was normal and ECG showed RBBB (Figure 1). A Troponin T (qualitative) test along with cardiac enzymes was done in view of possible acute coronary syndrome which were noncontributory as well. The patient was given symptomatic treatment by the resident on duty but on the second day he returned back with a vesicular eruption in the upper part of the trunk on the right side which extended to the axilla and the right mammary area (Figures 2a, b).